The Effect of Financial Literacy and Trust on the Interest of Millennials in Using Sharia Insurance - Arinal Rahmati (Kartika: Jurnal Studi Keislaman, 2025)
The objective of this study is to determine (1) the effect of financial literacy and (2) the effect of trust on the interest of the millennial generation in using sharia insurance. This study uses a quantitative approach. The population in this study is the community that belongs to the millennial generation who use sharia insurance. Sampling was conducted using a non probability sampling method with a purposive sampling technique. This study uses primary data sources with data collection through online questionnaires/Google forms. Data analysis in this study uses Smart PLS 3.2.9. The data analysis methods used in this study include validity tests, reliability tests, coefficient of determination (R2), hypothesis testing, and path analysis. The results of the study indicate that financial literacy does not have a significant effect on the interest of millennials in using sharia insurance, while trust has a significant effect on the interest of millennials in using sharia insurance. Financial literacy and trust can explain the interest in using sharia insurance by 35.9%, while the remaining 64.1% is explained by other variables that were not studied. It is hoped that future research will include more independent variables, so that the influence of other variables on the interest in using Islamic insurance among millennials can be determined.